KARAKTERISTIK PROKSIMAT DAN MINERAL TEPUNG KEPALA UDANG WINDU (Penaeus monodon) DENGAN PERENDAMAN FAAS (Filtrat air abu sekam) - Gebi, Gebi; Mismawati, Andi; Hasanah, Rafitah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2025)
Tiger shrimp heads represent a by-product of the processing industry that is not currently utilized. The substantial volume of tiger shrimp production gives rise to a considerable number of by-products, which pose environmental concerns if not properly managed, particularly with regard to the release of odors and the degradation of environmental aesthetics. One potential solution to address these issues is the utilization of tiger shrimp heads as a component of flour production. Shrimp head flour, a preserved product in dry form, is typically ground into flour. Tiger shrimp heads contain chitin, with levels ranging from 15% to 20%. This high level of chitin poses challenges during processing, particularly in the production of flour for use as a raw material in feed. The objective of this study is to ascertain the proximate and mineral composition of tiger shrimp head flour through the use of different concentrations of FAAS (husk ash water filtrate). This study used RAL with three replications and three treatments namely G1 (10% FAAS), G2 (20% FAAS) and G3 (30% FAAS) and G0 (no soaking) as control with 24 hours soaking time. Parameters observed included proximate and mineral. The results showed that shrimp head flour with FAAS soaking produced proximate and mineral characteristics that varied in each treatment, where the yield was (18.2%-22.8), water (5.24%-8.30%), ash (24.44%-25.35%), fat (3.75%-6.43%), protein (44.90%-50.49%), carbohydrate (11.54%-21.85%0), crude fiber (9.77%-13.67%), calcium (2.07%-2.93%), phosphorus (1.15%-1.54%) magnesium (0.31%-0.21).